Koordinasi Penyelenggaraan Tugas Pembantuan Di Kabupaten Bangka - KARYANA, AYI (Jurnal Studi Pemerintahan, 2012)
The study aims to describe and analyze: (1) coordinate the implementation of co-administration inBangka Regency; and (2) obtain a picture of the coordination function implemented in co-operation inthe Regency of Bangka. The method used in this research is descriptive analysis on the basis of aninterpretive approach. The results showed, in co-coordinating the implementation of Bangka regencybetween the Local Government Unit (SKPD) as the executor of the affairs of Co-administration (TP)and that the coordination of development planning, and funders (Provincial and Central) are not wellcoordinated. In the sense of coordination is still weak, it does not function according to the procedurethat should be. Lack of coordination can lead to programs and activities of TP can not fully achieve thegoals, and objectives are clear, in addition to the cost requirements, facilities and infrastructure, resourcerequirements needed to ensure the success of the TP has not been properly analyzed andmeasured in accordance with local capabilities.